HUBUNGAN PENGETAHUAN DAN PERILAKU PENCEGAHAN PENULARAN PENYAKIT KUSTA DI WILAYAH KERJA PUSKESMAS TANJUNGANOM KABUPATEN NGANJUK - Tamsuri, Anas (Jurnal AKP, 2010)
Leprae is a chronic communicable disease caused by Mycobacterium Leprae. The spreading of thedisease is strongly related to the patientâs attitude. The knowledge of the patient may affect patients in theirmanner on prevent of the spreading of the disease.The objective of the research was to investigate the relationship between the knowledge and the attitudeof the patients at working area of Public Health Centre of Tanjunganom, Nganjuk District.Research method was qualitative by cross-sectional design. It was conducted on May to July 2007 atworking area of Public Health Centre of Tanjunganom, Nganjuk Distric, The subject of the study was all 44patients. Data were gathered through questionnaire and they were analyzed by correlation test.The result of the study by spearman correlation with ï¡=0,05 returned the correlation coefficient 0,616with significance level =0,000 which mean that there was a moderate correlation between the knowlede andthe attitude of the patient of Leprae at working area of Public Health Centre of Tanjunganom, NganjukDistrict.Based on the result of the study, it was suggested to the patient to improve their knowledge by seekinformation about their disease and to health care personals to actively inform the disease and theprevention behavior of the disease, especially to the patients and its relatives.